Risk Factors for Continued Opioid Use in Conservative Versus Surgical Management of Low Back Pain Originating From the Sacroiliac Joint. Issue 5 (August 2018) - Dengler, Julius; Sturesson, Bengt; Kools, Djaya; Prestamburgo, Domenico; Cher, Daniel; van Eeckhoven, Eddie; Erk, Emanuel; Gasbarrini, Alessandro; Pflugmacher, Robert; Vajkoczy, Peter
Study Design: Secondary analysis of data from a randomized controlled trial. Objectives: To identify risk factors for continued opioid use after conservative management (CM) or minimally invasive surgical management (MISM) of low back pain (LBP) originating from the sacroiliac joint. Methods: Patients were randomized either to CM (n = 49) or MISM (n = 52). We documented opioid use, pain intensity (visual analogue scale [VAS]), Oswestry Disability Index (ODI), and the Zung depression score (Zung Self-Rating Depression Scale) at baseline and at months 3 and 6 after treatment initiation. Results: Compared with opioid nonusers, opioid users at baseline had higher mean levels of disability (ODI 61.5, standard deviation [SD] 13.3 vs ODI 51.5, SD 12.8; P < .01) and higher depression scores (Zung 48.5, SD 8.5, vs Zung 42.2, SD 7.2; P < .01). At 6 months, opioid users had higher 6-month pain levels (VAS 60.4, SD 24.0, vs VAS 42.4, SD 28.2; P < .01), higher disability scores (ODI 50.5, SD 16.2, vs ODI 32.7, SD 19.3; P < .01) and higher depression scores (Zung 47.6, SD 8.0, vs Zung 38.8, SD 8.9; P < .01). Risk factors for continued opioid use at 6 months were patient age (odds ratio [OR] for age = 0.91; P = .02) and an increase in LBP (OR 1.08; P = .02) in the CM group and a lack of improvement in depression scores (OR 1.12; P = .03) in the MISM group. Conclusions: In our patient cohort, the risk of continued opioid use in the treatment of LBP increased not only with pain intensity but also with levels of depression during the course of treatment.